2016
DOI: 10.1111/jdv.13644
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic urticaria and hormones: Is there a link?

Abstract: It would appear that sex hormones act as a trigger in only a small subset of women with CU. Nevertheless, this should be taken into account to improve patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In a cross‐sectional study that included interviewing 200 women with CU, it was observed that the disease occurred more often after the puberty and it worsened in four of 16 women during pregnancy, whereas hormonal contraception exacerbated CSU in 10% . The authors concluded that sex hormones act as a trigger in only a small subset of women with CU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross‐sectional study that included interviewing 200 women with CU, it was observed that the disease occurred more often after the puberty and it worsened in four of 16 women during pregnancy, whereas hormonal contraception exacerbated CSU in 10% . The authors concluded that sex hormones act as a trigger in only a small subset of women with CU.…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study that included interviewing 200 women with CU, it was observed that the disease occurred more often after the puberty and it worsened in four of 16 women during pregnancy, whereas hormonal contraception exacerbated CSU in 10%. 15 The authors concluded that sex hormones act as a trigger in only a small subset of women with CU. CSU exacerbated by oestrogens should be distinguished from hereditary angio-oedema type III, which is oestrogen-dependent, and is associated with normal levels of C1 inhibitor.…”
Section: Clinical Markers Of Severity and Time To Remissionmentioning
confidence: 99%
“…Epidemiological studies showed that most CSU patients are females between 20 and 59 years old and being female seems to be a predictor of longer time of remission and quality of life impairment 89,92,93. Although studies are limited, it appears that sex hormones could play a role as triggers of the disease in a small subset of patients 94. Most of the women studied did not experience CU before puberty; worsening symptoms was observed in a small group of pregnant women during urticaria, and hormonal contraception was associated with aggravation of symptoms in a minority of women 94.…”
Section: Clinical Biomarkersmentioning
confidence: 99%
“…Although studies are limited, it appears that sex hormones could play a role as triggers of the disease in a small subset of patients 94. Most of the women studied did not experience CU before puberty; worsening symptoms was observed in a small group of pregnant women during urticaria, and hormonal contraception was associated with aggravation of symptoms in a minority of women 94. Furthermore, a decreased serum concentration of dehydroepiandrosterone sulphate (DHEA-S) was observed in CSU patients, with levels significantly lower in symptomatic patients than in disease remission 95,96.…”
Section: Clinical Biomarkersmentioning
confidence: 99%
“…Different studies have described different clinical markers of severity and prognosis; few datasets show how age could be inversely associated with disease severity; the less old the patient is, the less severe the disease [2]. Being female seems to be a predictor of longer time to remission [26] and quality of life impairment [27]; in fact, as demonstrated by Amsler et al, urticaria onset occurs more often after puberty, is worsened by pregnancy, and could be reactivated by hormonal contraception [28]. However, the authors do not describe sex hormones as a pathogenic factor but only as a strong trigger in a small subset of patients [28].…”
Section: Severity and Prognosismentioning
confidence: 99%